Express Immunochromatographic Detection of Rotavirus and Adenovirus Antigens in Pre-Hospital Differential Diagnosis of Acute Abdominal Pain in Children - Ekaterina A. Romanova; Leyla S. Namazova-Baranova; Elena Yu. Dyakonova; Aleksey Yu. Romanov; Kazbek S. Mezhidov; Zharadat I. Dohshukaeva (Педиатрическая фармакология)
Background. The assessment of the condition of a child with acute abdominal pain and a diagnostic search algorithm at the prehospital stage determine the further routing of the patient and the timeliness of healthcare delivery. Objective. Our aim was to evaluate the possibility of using immunochromatographic rapid tests (ICA) to determine the rota- and adenovirus infection in pre-hospital differential diagnosis of abdominal syndrome in children. Methods. In a retrospective cohort study, we analyzed the medical records of patients with a combination of abdominal and intestinal syndromes who applied for medical assistance to the emergency pediatric department of the FSAI “NMRC of Children’s Health” of the Ministry of Health of Russia from January 2015 to December 2017. Results. Outpatient medical records of 201 patients aged from 4 months to 17 years have been analyzed. In patients with a positive ICA, only 6% (5/88) of cases had doubtful or positive symptoms of peritoneal irritation, whereas in the case of a negative rapid test, almost all children needed a surgeon’s consultation. The frequency of leukocytosis detection in a clinical blood test was not different in patients with different results of ICA. The increase of C-reactive protein as a marker of bacterial inflammation was more common in patients with a negative rapid test. The volume of additional diagnostic care in the group of patients with a negative ICA result was significantly higher than in patients with confirmed viral gastroenteritis. None of the children with confirmed viral gastroenteritis required a surgical treatment. In the group with a negative ICA result, surgical treatment was performed in 11% (12/113) cases. Conclusion. Patients with confirmed viral gastroenteritis require significantly fewer diagnostic measures; they also have a minimal probability of acute surgical pathology. The use of laboratory rapid tests at the pre-hospital stage plays an important role in the timely diagnosis and the reduction in the frequency of non-specialized hospitalization.